Esperienza e scienza: quale rottura epistemologica? - Costa, Vincenzo (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
Bachelard’s historical epistemology sets a challenge for the phenomenological philosophy. If the modern sciences are to be understood as “phenomenotechnologies” then phenomenal experience seems to become useless. This paper tries to outline the guidelines of a phenomenological analysis of the interrelationships between science as historical sedimentation and phenomenal experience. It must provide a criterion for interpreting the processes which lead from the intuitively given surrounding world to the idealization of the science. Keywords: Phenomenology, Life-world, Science, Phenomenotechnologies, Idealization.